Media Literation Model for Development of Tolerance and Multicultural Attitudes in The Students of Universitas Negeri Semarang - Utomo, Cahyo Budi; Astuti, Tri Marhaeni Pudji; Kurniawan , Edi (KnE Social Sciences, 2019)
Indonesia is a multicultural country that consists of various races, ethnicities, customs, cultures, ethnicities, languages, and gender that are different from one another. Multicultural communities prioritize differences in equality. This condition is reinforced bytheexistenceofslogans“Bhinekatunggalika”.Becauseofthisdiversityisoursocial capital for life with respects and tolerance each other also acknowledges equality. However, the phenomenon of intolerance issues which latterly emerged in Indonesia, has created an atmosphere of injury to diversity. The problem is not only triggered by internal friction between the elements of the nation, but also is a part of the reﬂection of global conditions in the contemporary era as if no longer geographically isolated because of the ease of access to information through the sophistication of its technology. There is an ideological network that unites to develop participation in variouscountriesintheworld.ThisresearchwasconductedonstudentsofUniversitas Negeri Semarang (UNNES). If students can build tolerance and multicultural values, it is expected to minimize the incidence of intolerance in the future. The objectives in this study are: 1) Knowing the implementation of the media literacy movement at Universitas Negeri Semarang. 2) Develop a media literacy model and the strategy for implementingmedialiteracymodelsforthedevelopmentofmulticulturaltoleranceand values among students. Outcomes of research: 1) Making articles on scientiﬁc journal publications. 2) Arranging Textbooks. The research method uses qualitative research and is a Research and Development. Keywords: media literacy, multicultur, tolerance, intolerance